Enhancing Efficacy of TCR-engineered CD4+ T Cells Via Coexpression of CD8α. Issue 4 (27th May 2023) - Anderson, Victoria E.; Brilha, Sara S.; Weber, Anika M.; Pachnio, Annette; Wiedermann, Guy E.; Dauleh, Sumaya; Ahmed, Tina; Pope, George R.; Quinn, Laura L.; Docta, Roslin Y.; Quattrini, Adriano; Masters, Siobhan; et al.
Abstract : Adoptive cell therapy with T cells expressing affinity-enhanced T-cell receptors (TCRs) is a promising treatment for solid tumors. Efforts are ongoing to further engineer these T cells to increase the depth and durability of clinical responses and broaden efficacy toward additional indications. In the present study, we investigated one such approach: T cells were transduced with a lentiviral vector to coexpress an affinity-enhanced HLA class I–restricted TCR directed against MAGE-A4 alongside a CD8α coreceptor. We hypothesized that this approach would enhance CD4 + T-cell helper and effector functions, possibly leading to a more potent antitumor response. Activation of transduced CD4 + T cells was measured by detecting CD40 ligand expression on the surface and cytokine and chemokine secretion from CD4 + T cells and dendritic cells cultured with melanoma-associated antigen A4 + tumor cells. In addition, T-cell cytotoxic activity against 3-dimensional tumor spheroids was measured. Our data demonstrated that CD4 + T cells coexpressing the TCR and CD8α coreceptor displayed enhanced responses, including CD40 ligand expression, interferon-gamma secretion, and cytotoxic activity, along with improved dendritic cell activation. Therefore, our study supports the addition of the CD8α coreceptor to HLA class I–restricted TCR-engineered T cells to enhance CD4 + T-cell functions, which may potentially improve the depth and durability of antitumor responses in patients.